Pythagorean Fuzzy AHP Based Dynamic Subcontractor Management Framework - Basaran, Yunus; Aladag, Hande; Isik, Zeynep (MDPI, 2023)
In construction projects, a significant part of construction work is done by subcontractors (SCs). Therefore, their management by main contractors (MCs) becomes an important issue as the density of SCs is created at the construction sites. In recent years, more focus on SC evaluation and selection in bidding process has been on the agenda whereas the subject of SC performance appraisal on-site during the project execution phase has been untended in the literature. Thus, this study aims to focus on the measurement and evaluation of the performance of SCs in the project execution phase, and to provide a tentative performance-based dynamic management framework that MCs will use in the management of SCs in order to take proactive measures. In line with the aim, a total number of 23 performance measurement criteria (PMC) under 7 main groups were determined as a result of a comprehensive literature review and expert evaluations. Knowing that not every criterion will have the same effect in performance measurement, pairwise comparisons of the criteria were made using the Pythagorean Fuzzy Analytic Hierarchy Process (PFAHP) method and their importance weights were determined. The PFAHP method was obtained by integrating the Pythagorean fuzzy set into the AHP method and chosen with the aim of improving the fuzzy AHP method and obtaining more consistent results by eliminating the uncertainty since Pythagorean fuzzy sets is more capable than fuzzy sets at expressing and handling uncertainty in uncertain environments. Lastly, a framework for SC performance measurement and evaluation on project execution phase is presented. It is believed that the presented framework will allow for a proactive management style that will enable effective decisions to be made while the project is ongoing, and a dynamic way of working instead of static and conventional work.
Keywords: subcontractor management; performance measurement criteria; performance appraisal; Pythagorean Fuzzy Analytic Hierarchy Process (PFAHP); project execution phase; SUB-CONTRACTOR SELECTION; CRITICAL SUCCESS FACTORS; DECISION-MAKING; CONSTRUCTION PROJECTS; PERFORMANCE; CRITERIA; LEADERSHIP; IDENTIFICATION; APPRAISAL; SYSTEM; Construction & Building Technology; Engineering